2019
DOI: 10.1111/acer.14029
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Effects of Alcohol: A Review of Paternal Preconception Ethanol Exposure Studies and Epigenetic Mechanisms in the Male Germline

Abstract: While alcohol use disorder (AUD) is a highly heritable psychiatric disease, efforts to elucidate that heritability by examining genetic variation (e.g., single nucleotide polymorphisms) have been insufficient to fully account for familial AUD risk. Perhaps not coincidently, there has been a burgeoning interest in novel nongenomic mechanisms of inheritance (i.e., epigenetics) that are shaped in the male or female germ cells by significant lifetime experiences such as exposure to chronic stress, malnutrition, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 160 publications
2
55
0
Order By: Relevance
“…For example, the intergenerational effects of stress [ 59 , 62 ], high fat diet [ 60 ], environmental enrichment [ 61 ], and trauma [ 63 , 64 ] are all mediated by changes in sperm noncoding RNAs. Several studies have reported that alcohol can act as an epimutagen and has the ability to induce alterations in DNA methylation, chromatin modifications, and noncoding RNAs in sperm (for review, see: [ 11 ]). Previous studies from our laboratory [ 35 ] and others [ 65 ] found that chronic ethanol exposure altered several small noncoding RNAs including tRNA derived fragments, PIWI-interacting RNAs, and miRNAs in sperm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the intergenerational effects of stress [ 59 , 62 ], high fat diet [ 60 ], environmental enrichment [ 61 ], and trauma [ 63 , 64 ] are all mediated by changes in sperm noncoding RNAs. Several studies have reported that alcohol can act as an epimutagen and has the ability to induce alterations in DNA methylation, chromatin modifications, and noncoding RNAs in sperm (for review, see: [ 11 ]). Previous studies from our laboratory [ 35 ] and others [ 65 ] found that chronic ethanol exposure altered several small noncoding RNAs including tRNA derived fragments, PIWI-interacting RNAs, and miRNAs in sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, rodent studies have demonstrated that paternal preconception ethanol (PPE) exposure leads to molecular, cellular, physiological, and behavioral abnormalities in offspring (for reviews, see: [ 11 , 12 ]). For example, PPE-sired offspring exhibited insulin hypersensitivity and upregulated transforming growth factor beta signaling [ 13 ], altered enzymes and proteins involved in metabolism and weight gain [ 14 ], and altered levels of neurotrophins like brain-derived neurotrophic factor and nerve growth factor [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fertility rates of male rats ingesting alcohol were demonstrated to be lower than those of the control group [34]. Other studies reported similar results, describing detrimental effects on mitochondria, with a significant increase in ROS generation, and observing epigenetic modifications in the germline [35,36]. In addition, different studies have shown that chronic ethanol intake has been related to a decrease of cell proliferation in testes; to the induction of testicular apoptosis, increasing the Fas ligand and upregulating p53 gene expression; and to epididymal damage [37][38][39].…”
Section: Alcohol and Tobaccomentioning
confidence: 84%
“…Recent evidence suggests that epigenetic modifications can be carried to the offspring via the germline and are responsible for the transmission of alcohol-related disorders across generations ( Mahnke, Miranda & Homanics, 2017 ; Chastain & Sarkar, 2017 ). Interestingly, there are studies showing the association of parental alcohol intake with subsequent changes in gene expression in naïve offspring ( Rompala & Homanics, 2019 ; Kim et al, 2014 ; Asimes et al, 2017 ), as well as with changes in lipid metabolism ( Przybycien-Szymanska et al, 2014 ). Moreover, Pennington, Shuvaeva & Pennington (2002) showed that maternal preconceptional alcohol intake may be associated with hypertriglyceridemia in adult offspring who have never been exposed to alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…However, apart from reports on maternal alcohol use during pregnancy or in the periconceptional period, studies on paternal preconception alcohol exposure on offspring also provide interesting findings. Paternal alcohol intake during the preconception period induces a spectrum of health problems and alters gene expression in rodent offspring ( Knezovich & Ramsay, 2012 ; Finegersh et al, 2015 ; Jabbar et al, 2016 ; Rompala & Homanics, 2019 ). The results of the study of Kim et al (2014) suggest that the preconceptional exposure to ethanol of male mice before mating induces ADHD-like behaviours in offspring, possibly via epigenetic changes in gene expression.…”
Section: Introductionmentioning
confidence: 99%